Gene Delivery via Octadecylamine-Based Nanoparticles for iPSC Generation from CCD1072-SK Fibroblast Cells - Varli, Hanife Sevgi; Akkurt Yildirim, Meryem; Kizilbey, Kadriye; Turkoglu, Nelisa (MDPI, 2024)
This study presents a novel biotechnological approach using octadecylamine-based solid lipid nanoparticles (OCTNPs) for the first-time reprogramming of human CCD1072-SK fibroblast cells into induced pluripotent stem cells (iPSCs). OCTNPs, with an average size of 178.9 nm and a positive zeta potential of 22.8 mV, were synthesized, thoroughly characterized, and utilized as a non-viral vector to efficiently deliver reprogramming factors, achieving a remarkable transfection efficiency of 82.0%. iPSCs were characterized through immunofluorescence, flow cytometry, and RT-qPCR, confirming the expression of key pluripotency markers such as OCT4, SOX2, and KLF4, with alkaline phosphatase activity further validating their pluripotent state. Following this comprehensive characterization, the iPSCs were successfully differentiated into cardiomyocyte-like cells using 5-azacytidine. Our research highlights the innovative application of OCTNPs as a safe and effective alternative to viral vectors, addressing key limitations of iPSC reprogramming. The novel application of OCTNPs for efficient gene delivery demonstrates a powerful tool for advancing stem cell technologies, minimizing risks associated with viral vectors. These findings pave the way for further innovations in biotechnological applications, particularly in tissue engineering and personalized medicine.
Keywords: nanoparticle-mediated gene delivery; biotechnology; cell culture; reprogramming; PLURIPOTENT STEM-CELLS; SMALL MOLECULES; DIFFERENTIATION; MATRIGEL; SYSTEM; Biochemistry & Molecular Biology